Effect of stage 2 kindling on local cerebral blood flow rates in rats with genetic absence epilepsy - ONAT, FİLİZ; GÜLHAN, REZZAN (WILEY, 2009)
Genetic absence epilepsy rats from Strasbourg (GAERS) are resistant to the progression of kindling seizures. We studied local cerebral blood flow (LCBF) changes in brain regions involved in seizures in both GAERS and nonepileptic rats (NEC) to map the differences that may be related to the resistance to kindling. Electrodes were implanted in the amygdala of adult NEC and GAERS male rats, which were stimulated to reach stage 2. Quantitative autoradiographic measurements of LCBF were performed by the [C-14]-iodoantipyrine ([C-14]IAP) autoradiographic technique allowing the precise mapping of regional perfusion changes. LCBF rates were measured bilaterally in 43 brain regions. The tracer infusion lasted for 60 s and started at 15 s before seizure induction. Rates of LCBF increased in stimulated GAERS and NEC groups compared to nonstimulated controls. The LCBF increase in stimulated GAERS was larger and more widespread than that observed in stimulated NEC. The LCBF increase in the somatosensory cortex, ventrobasal and anterior thalamic nuclei, hypothalamus, subthalamic nucleus, piriform, entorhinal and perirhinal cortex, amygdala, CA2 region of hippocampus, and substantia nigra was statistically significantly larger in stimulated GAERS compared to stimulated NEC rats. The results show that more brain regions are activated by kindling stimulation in GAERS. This widespread activation in GAERS involves the somatosensory cortex and thalamus, which are both known to be involved in the expression of absence seizures as well as numerous limbic regions thought not to play a role in the expression of absence seizures, suggesting an interaction between corticothalamocortical and limbic circuitries.
Keywords: Limbic seizures; Epileptogenesis; Kindling-resistance; Spike-and-wave discharges; [C-14]-iodoantipyrine; ELECTRICAL-STIMULATION; ENTORHINAL CORTEX; WAVE DISCHARGES; TEMPORAL-LOBE; SEIZURES; MODEL; BRAIN; METABOLISM; MECHANISMS; GLUTAMATE